Application Of AnnAGNPS Model For Soil Loss Estimation And Utrients Loading For Malaysian Conditions - Leow, Cheng Siang (Universiti Sains Malaysia, 2006)
Non-point source (NPS) pollution is one of the major sources of contribution of pollutants to watersheds and stream water. Although awareness has increased in Malaysia over the last few decade, there is still no unified system that can continuously monitor and evaluate watersheds in the country. Most studies are limited to short-term evaluation and do not provide long-term monitoring. This study aims to apply AnnAGNPS watershed modelling to assess NPS pollution in three selected watersheds. Rainfall data of 2004 and 2005 are used to calibrate and validate the model. The results of simulation are generally satisfying. Runoff estimation could reach a coefficient of determinacy of 0.73, and event based sediment yield produced 2 R of 0.57. The average annual erosion rate of studied area is 62 Mg/ha/yr for 2004 and 123Mg/ha/yr for 2005. The distribution erosion is in agreement with the National Erosion Risk Map. N and P predictions are slightly inconsistent with 2 R =0.69 and 0.64 respectively but with high standard deviation. The study is able to detect rubber estate and urban land as major contributor to soil erosion. Rubber estate is also the main contributor for nitrogen loading. The study also identifies LS factor to be the most sensitive parameter in influencing erosion and sediment yield. Error and inconsistency can be caused by reference data that may be not suitable for local condition. The average result shows that AnnAGNPS is able to perform well under Malaysian condition and can do even better if proper improvements are made. A database should be set up to aid local research in improving watershed study, particularly AnnAGNPS.